A contemporary social contract: An exploration of enabling factors influencing climate policy intractability in developed nations. Issue 5 (5th August 2022) - Groff, Stephen P.
Abstract: The social contract has long been used to describe the advantages of individual submission to the body politic. Although a considerable focus has been dedicated to the individual affordances of the social contract, less attention has been paid to the factors that condition individuals' willingness to sacrifice for the collective. For scholars of political science, it is useful to understand the social contract's enabling factors, those conditions which motivate constituent support for public policies and influence citizens' willingness to limit individual freedoms in exchange for greater social security and assurances of collective wellbeing. In this paper, it is theorized that citizens lend their trust to public institutions to enable a social contract. Further, it is hypothesized that individuals who exhibit stronger enabling factors are more likely to contribute to a global conceptualization of the social contract that is committed to international climate policy objectives. Toward that end, an exploratory and descriptive analysis of several existing data sets examines the relationship between the enabling factors of public trust and the outcomes of environmental policy to survey the strength of variable associations that condition support for international climate policy commitments necessary to maintaining a contemporary social contract (CSC).